2018
DOI: 10.1159/000495655
|View full text |Cite
|
Sign up to set email alerts
|

Successful Certolizumab Pegol Treatment of Chronic Anterior Uveitis Associated with Psoriasis Vulgaris

Abstract: This report presents details on a 45-year-old male Japanese patient with chronic and refractory anterior uveitis associated with psoriasis vulgaris who was administered certolizumab pegol (CZP), which is an anti-tumor necrosis factor alpha (TNF-α) monoclonal antibody. Although CZP has only been formally approved for rheumatoid arthritis treatment in Japan, a clinical trial allowed us to assess CZP effectiveness in this patient. The grade 3+ anterior chamber inflammation (for both the cells and flare) observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Additionally, chronic anterior uveitis associated with psoriasis vulgaris successfully treated with certolizumab pegol has been reported. 8 However, some patients do not benefit from anti-TNF therapy. Whether the uveitis in our patient is related to the use of etanercept or infliximab remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, chronic anterior uveitis associated with psoriasis vulgaris successfully treated with certolizumab pegol has been reported. 8 However, some patients do not benefit from anti-TNF therapy. Whether the uveitis in our patient is related to the use of etanercept or infliximab remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…It was found to effectively settle active inflammation in five out of seven patients with no adverse effects encountered, leading to the suggestion that certolizumab may be of use in the management of NIU . A case study from Japan has likewise confirmed resolution of anterior uveitis associated with psoriatic arthritis treated with certolizumab …”
Section: Current Therapiesmentioning
confidence: 96%
“…106 A case study from Japan has likewise confirmed resolution of anterior uveitis associated with psoriatic arthritis treated with certolizumab. 107 A large phase 3 randomized trial involving the use of certolizumab in 325 patients with axial spondyloarthritis for up to 4 years showed a relatively good safety profile with serious adverse events occurring in only 21.9% of the population. Along with the complications associated with TNF inhibition, common effects of certolizumab include GI irritation, increased risk of infection and elevated liver function tests.…”
Section: Certolizumabmentioning
confidence: 99%
“…Recent emerging and adopted therapies, including tocilizumab (STOP study),[ 67 ] sarilumab (SATURN study),[ 68 ] and S irolimus as a Therapeutic A pproach UVE itis (SAVE)-2 study (sirolimus),[ 69 ] have shown encouraging outcomes of these agents in the treatment of NIU with regard to minimizing corticosteroid dosage, reducing vitreous haze score (≥2 steps), and improving visual acuity with a relatively benign safety profile. However, other therapies such as secukizumab (INSURE study),[ 70 ] gevokizumab (EYEGUARD study),[ 71 ] ustekizumab (STELABEC study), apremilast,[ 74 ] and sotrastaurin[ 73 ] have shown no difference in the recurrence rate between placebo and treatment groups or lack of efficacy. Other promising therapies, including certolizumab,[ 74 ] canakinumab,[ 75 ] anakinra,[ 76 ] IFN-α,[ 77 78 79 ] abatacept,[ 80 81 82 83 84 85 ] filgotinib,[ 86 ] tofacitinib,[ 87 ] alemtuzumab,[ 88 89 ] and adrenocorticotropic hormone[ 90 ] have demonstrated efficacy in small case reports.…”
Section: Immunosuppressive Agentsmentioning
confidence: 99%
“…However, other therapies such as secukizumab (INSURE study),[ 70 ] gevokizumab (EYEGUARD study),[ 71 ] ustekizumab (STELABEC study), apremilast,[ 74 ] and sotrastaurin[ 73 ] have shown no difference in the recurrence rate between placebo and treatment groups or lack of efficacy. Other promising therapies, including certolizumab,[ 74 ] canakinumab,[ 75 ] anakinra,[ 76 ] IFN-α,[ 77 78 79 ] abatacept,[ 80 81 82 83 84 85 ] filgotinib,[ 86 ] tofacitinib,[ 87 ] alemtuzumab,[ 88 89 ] and adrenocorticotropic hormone[ 90 ] have demonstrated efficacy in small case reports. Phase 2 clinical trials evaluating the safety and efficacy of filgotinib,[ 77 ] tofacitinib,[ 87 ] and adrenocorticotropic hormone[ 90 ] in NIU are currently ongoing.…”
Section: Immunosuppressive Agentsmentioning
confidence: 99%